Cultural diversity in maternity care in improving the quality of care services: a systematic review - Iswanti, Dwi Indah; Erwansyah, Rio Ady; Saifudin, I Made Moh. Yanuar; Pujiyanto, Tri Ismu (Intelektual Pustaka Media Utama, 2024)
This study aimed to elucidate the significance of cultural diversity in maternity care in the context of enhancing the quality of care services. To undertake this systematic review, we conducted searches across multiple databases, including CINAHL, SAGE, ScienceDirect, ProQuest, Scopus, and Springer. The process of article selection was executed through Science Direct and Sage, with adherence to specific inclusion criteria, such as articles published within the last five years, written in English, and focusing on maternity care. This study excluded articles with unclear literature reviews and those written in languages other than English. To analyze the risk of bias and the caliber of the included articles, we used the JBI assessment checklist and the PRISMA flow chart. A total of 20 relevant articles were selected for review. In order to enhance the quality of maternity care services, it is imperative to consider a range of facets, including showing respect and tolerance for cultural diversity, fostering effective communication, and honing relevant skills. Maternity care providers must cultivate an attitude of respect and tolerance towards the cultural diversity of their patients and their families.